Download presentation
Presentation is loading. Please wait.
Published byIsaac McDonald Modified over 9 years ago
1
Aim: How do we multiply a monomial by a monomial? Do Now: Multiply: 1. 3 · 3 · 3 2. x · x 3. 3x · 2x 4. x³ · x² 5. (4x 2 ) 2
2
3 · 3 · 3 = 3 3 = 27 3 is just the same as 3 1+1+1 Therefore, we just need to add the exponents when we multiply the monomials with the same bases Use the same idea to multiply the monomials with the same variable bases x · x = x 1+1 = x 2
3
To multiply a monomial by another monomial with the same bases 1. multiply the coefficients 2. multiply the same variables by adding the exponents 3. Multiply the exponents if the power of a monomial to another power (such as Do Now #5)
4
6. 2x · 3x²y = 6x³y 7. (-7a²b³)(-4a²b) 8. (3xy)² this is the same as 3xy · 3xy 9. (8a²b)(3cd²) 10. (-2x 2 y 3 ) 2 = 28a 4 b 4 = 3xy · 3xy = 9x²y² = 24a²bcd² = 4x 4 y 6
5
1. s · s 2. y · y² 3. 3 · 3³ 4. (y³)² 5. (5a²)(-4a²) 6. (-6x³)(-3x)
6
7. (3z²)(-5y²z) 8. (-9c)(8cd³) 9. (-2a³)(5a)(-4a²) 10. -3xy 2 (2x 2 y 3 ) 11. 4x(x 2 y 2 ) 3
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.